2021
DOI: 10.1037/adb0000619
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of lapses and recoveries during a quit attempt using varenicline and behavioral counseling among smokers with and without HIV.

Abstract: Addressing tobacco use among HIVϩ smokers is a priority. Lack of knowledge about how HIVϩ smokers respond to tobacco use treatments limits our ability to effectively treat this population of smokers. Using data from 2 clinical trials that provided 12 weeks of varenicline and behavioral counseling, 1 with smokers with HIV (n ϭ 89) and 1 with smokers without HIV (n ϭ 179), we used mixed logistic regression modeling to compare point-prevalence abstinence rates and adherence to the initial target quit date (TQD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…[64,65] Similarly, Ashare and colleagues completed a trial of varenicline compared to placebo in PWH and noted that varenicline was superior to placebo at the close of treatment (PPA: 28.1% vs. 12.1%; Δ = 16.0%). [26] Further, dual NRT (long term patch + ad lib NRT) was similarly efficacious for abstinence at 6 months post quit as varenicline [dual NRT: abstinent = 36.5% (95% Confidence Interval [CI] = 28-45) and varenicline abstinent = 33.2% [29][30][31][32][33][34][35][36][37][38]]. [13] Sample size will be based on a conservative estimate of the effect sizes provided above (Δ = 17%).…”
Section: Power and Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…[64,65] Similarly, Ashare and colleagues completed a trial of varenicline compared to placebo in PWH and noted that varenicline was superior to placebo at the close of treatment (PPA: 28.1% vs. 12.1%; Δ = 16.0%). [26] Further, dual NRT (long term patch + ad lib NRT) was similarly efficacious for abstinence at 6 months post quit as varenicline [dual NRT: abstinent = 36.5% (95% Confidence Interval [CI] = 28-45) and varenicline abstinent = 33.2% [29][30][31][32][33][34][35][36][37][38]]. [13] Sample size will be based on a conservative estimate of the effect sizes provided above (Δ = 17%).…”
Section: Power and Sample Sizementioning
confidence: 99%
“…[26,27] Optimizing varenicline reach and clinical follow-up to improve adherence may help curb lapses/relapses and improve efficacy. [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Among PWH, tobacco use rates are 40-50% [4], nearly triple the 15.2% rate of combustible tobacco product use in the general U.S. population [5]. Prior research has shown that approximately 50% of PWH are interested in quitting and 89% have made a quit attempt once in their lifetime [6] but have difficulty achieving abstinence [7]. PWH who continue to smoke after their diagnosis are approximately 20% more likely to die from lung cancer than their societal counterparts [3].…”
Section: Introductionmentioning
confidence: 99%